2005
DOI: 10.1007/s00415-005-0853-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction in critical care for acute stroke: Severity of illness–score or coma–scale?

Abstract: SAPS II and SAPS (I) but also the GCS are valuable tools for prediction of short and long-term mortality in acute stroke patients treated in NCCU. The GCS as a predictor for mortality in stroke patients could be further simplified by using its subscore "best motor response" alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
4
22
2
Order By: Relevance
“…Most previous studies have focused on ICU or in-hospital mortality. However, short-term (≤ 3 months) mortality has been reported to be in the range 46 – 90% (7, 10, 11, 15, 16, 20, 3437); this compares to a 30-day mortality in our sample of 65%. Older and smaller studies have generally reported higher mortality rates.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Most previous studies have focused on ICU or in-hospital mortality. However, short-term (≤ 3 months) mortality has been reported to be in the range 46 – 90% (7, 10, 11, 15, 16, 20, 3437); this compares to a 30-day mortality in our sample of 65%. Older and smaller studies have generally reported higher mortality rates.…”
Section: Discussioncontrasting
confidence: 69%
“…Firstly, studies have been conducted in a number of countries, likely with differing practices in the intensive care unit management of stroke. Secondly, very small numbers of patients have been included, ranging from 58 to 138, mostly in single centers (35, 7, 8). Finally, there has been no uniformity in the type of stroke patient studied, with reports including either hemorrhagic stroke, ischemic stroke or both.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, coma at admission was a strong predictor of in-hospital mortality. In line with this finding, several studies demonstrated a correlation of initial GCS and short-term mortality [21,25,26] . However, only two studies including >100 patients -both originating from Asian countries -evaluated the NIHSS score in their patient collectives as a stroke-specific severity marker [16,25] .…”
Section: Discussion and Review Of The Literaturesupporting
confidence: 52%
“…Therefore the higher percentage of infratentorial lesions in the AS group should have resulted in a higher rather than a lower case fatality. However, populations have not been analyzed for the occurrence of the prognostic factors of morbidity of patient with stroke, such as Glasgow Coma Scale (Handschu et al, 2005) or cardiovascular risk factors.…”
Section: The Influence Of Differences Between Patient Groupsmentioning
confidence: 99%